ANALISIS LITERASI MATEMATIKA PESERTA DIDIK BERDASARKAN HOTS KELAS VII MTS SARJI AR-RASYID SITUBONDO - Rida Holifa; Zainul Munawwir; Irma Noervadila (STKIP PGRI Situbondo, 2020)
Mathematics education is closely related to every human being's everyday life, one of which is counting. Mathematics education also needs to be taught to students to be more disciplined, develop patterns of thinking from the usual to more than before, and read the problems faced and find solutions. This study aims to describe the students' scientific literacy based on HOTS according to the criteria of high, medium, and low-grade VII MTs Sarji Ar-Rasyid for the 2019/2020 academic year. The type of research used is descriptive qualitative. This study's subjects were three class VII students of MTs Sarji Ar-Rasyid based on high, medium, and low HOTS criteria. Data collection techniques were observation, HOTS test, mathematical literacy test, interviews, and documentation. The results of the Student Matematic Literacy analysis based on HOTS with high, medium, and low criteria showed different results. In research subjects with high criteria and moderate criteria have met the indicators of mathematical literacy, namely, expressing mathematical ideas orally and in writing, combining personal experiences related to mathematical problems, and utilizing the tools needed. Simultaneously, the research subjects with low criteria have not met the indicators of mathematical literacy by looking at the unsatisfactory results of the mathematics literacy test.